2015
DOI: 10.1590/1809-9823.2015.14080
|View full text |Cite
|
Sign up to set email alerts
|

Letramento funcional em saúde na perspectiva da Enfermagem Gerontológica: revisão integrativa da literatura

Abstract: Objective: To perform an integrative review of literature on functional health literacy from the perspective of Gerontological Nursing. Method: a study was made of the MEDLINE, PubMed, LILACS, IBECS, BDENF and CidSaúde databases, and studies published in Brazilian and international publications during the period of 2005-2014 were included. The studies were selected by main subject, such as education of patient, health literacy, schooling, the elderly, health education and self-care. Results: 58 studies were fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
18

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 31 publications
0
7
0
18
Order By: Relevance
“…11 It is important to highlight that FHL depends on multiple determinants inherent to individuals, such as sociodemographic characteristics, cognitive abilities and physical abilities, which interact with one another when considering the educational system, health system, cultural and social context. Such factors may make those individuals with little formal education, who are poorer and older more vulnerable, 15 such as those found in this research.…”
Section: Discussionmentioning
confidence: 79%
“…11 It is important to highlight that FHL depends on multiple determinants inherent to individuals, such as sociodemographic characteristics, cognitive abilities and physical abilities, which interact with one another when considering the educational system, health system, cultural and social context. Such factors may make those individuals with little formal education, who are poorer and older more vulnerable, 15 such as those found in this research.…”
Section: Discussionmentioning
confidence: 79%
“…This scenario refers to the importance of understanding the need for continuous monitoring of this public in order to achieve satisfactory health outcomes. [35][36] Thus, in order to increase the effects of health promotion, health professionals can aim to increase the health literacy levels of its target populations, thus obtaining better results and a more equal distribution of health indexes, as recommended by health care workers.…”
Section: Discussionmentioning
confidence: 99%
“…Over the past few years, studies have shown that chronic diseases control is not adequately predicted by formal schooling alone. Thus, a broader construct called functional health literacy emerged (1)(2) . Functional health literacy represents the ability to interpret texts and numbers that are usually present in test results or prescriptions, as well as in guidance leaflets (1)(2)(3)(4) .…”
Section: Introductionmentioning
confidence: 99%